2001
DOI: 10.1093/emboj/20.21.6127
|View full text |Cite
|
Sign up to set email alerts
|

Cdc13 prevents telomere uncapping and Rad50-dependent homologous recombination

Abstract: Cdc13 performs an essential function in telomere end protection in budding yeast. Here, we analyze the consequences on telomere dynamics of cdc13-induced telomeric DNA damage in proliferating cells. Checkpoint-de®cient cdc13-1 cells accumulated DNA damage and eventually senesced. However, these telomerase-pro®cient cells could survive by using homologous recombination but, contrary to telomerasede®cient cells, did so without prior telomere shortening. Strikingly, homologous recombination in cdc13-1 mec3, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
99
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 47 publications
14
99
0
Order By: Relevance
“…4). The mutant mec1⌬ sml1⌬ cdc13-1 had a slight higher permissive temperature (about 29°C), as previously reported (31). However, mec1⌬ sml1⌬ greatly reduced caspase activation (Fig.…”
Section: Mec1 Plays An Important Role In Mediating Apoptoticsupporting
confidence: 86%
“…4). The mutant mec1⌬ sml1⌬ cdc13-1 had a slight higher permissive temperature (about 29°C), as previously reported (31). However, mec1⌬ sml1⌬ greatly reduced caspase activation (Fig.…”
Section: Mec1 Plays An Important Role In Mediating Apoptoticsupporting
confidence: 86%
“…In yeasts and plants, homologs of CST appear to ensure telomere stability by capping chromosome ends [3,[11][12][13][14][15][16][17][18][19][20][21][22]. In vertebrates, the capping function is achieved by shelterin proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In yeasts and plants, homologs of CST are critical for ensuring telomere stability [3,[11][12][13][14][15][16][17][18][19][20][21][22]. In budding yeast, the Cdc13/Stn1/Ten1 complex associates exclusively with the G-overhang and plays important roles in restricting excessive C-strand resection from telomere ends, mediating C-strand fill-in, and regulating telomerase activity [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, deletion of EST1 and EST3 (two regulatory subunits of the telomerase complex), although causing telomere loss, failed to elicit the same accumulation in G-strand overhangs. Notably, the overhang increase is reminiscent of the phenotypes of Saccharomyces cerevisiae mutants suffering from dysfunction of telomere binding proteins such as Cdc13p, Ku70, and Ku80 (14)(15)(16)(17). Analysis of such mutants indicated that loss of telomere protection engenders preferential degradation of the telomere C-strand, leading to G-strand overhang accumulation (18)(19)(20).…”
mentioning
confidence: 99%